AS PERCEPÇÕES DE GÊNERO DAS MULHERES CAMPONESAS AFRODESCENDENTES NO MUNICÍPIO DE PICUÍ-PB - Silva, Francisca Aparecida Firmino da (2005)
His study consists of analyzing the descending farmers' of the black race perceptions about the gender relationships. We looked for to understand in that measured those women, that possess some form of political insert in social organizations, they give a new elaboration or not the gender relationships in the ambit of the family and domestic agriculture. We tried to analyze the descending farmers' of the black race understandings on what he/she is man and woman, to know, starting from those women's optics, as they are established the sexual divisions of the work in the ambits of the family and domestic agriculture; and which the perspectives that they appear for the construction of the balance among the sexes. The study contemplated fifteen resident women in the communities of Atanásio, Coruja and Pedreiras, inserted in the rural perimeter of the municipal district of Picuí PB (Brazil), participants of the Community Associations and Unions of the Rural Workers. The instruments that we used for the collection in data way: technique of free observation, semi-structured interviews recorded in ribbons cassettes, use of the field diary, besides the resource of the ethnography that served us of base for the selected communities' characterization and of the lifestyle developed by the women subject of the research. The results revealed that most of the women still possesses a conservative and patriarchal plenty understanding of the gender relationships, attributing to the man provider's paper, besides the control of the space of the house and of the family agriculture. With relationship to the understanding of being woman, the interviewees for the most part are placed in conformity position, living together with the suffering in a resigned way. The women's sufferings are referring to the lack of money, the companions' financial dependence, lack of water, concern with the children and with the husband, overload of tasks, besides the poverty situation in that live. Some women little by little have been waking up in the perspective of to give new meaning the gender relationships when they question the non collaboration of the husband in the domestic activities, the non valorization of the feminine work, the absence of freedom, the longing for paid work for if they turn independent economically of your husbands. Those few women signal for a new gender elaboration in the space of the family agriculture and in the space of the house, even if is still in a quite incipient way. Our study appeared that the gender relationships in the ambit of the family agriculture and in the domestic space it still follows the patriarchal model and few women get in a slow way to shimmer a new elaboration for the construction of the gender, tends as beginning the equality among the sexes.